A major practicum report at Nenita Quality Foods Corporation, Marapangi, Toril, Davao City - Nuqui, April Love de Toro (2009)
Part of the curriculum of the Bachelor of Science in Food Technology was the 288 hour of plant practice conducted at Nenita Quality Foods Corporation from April 16 to May 29, 2007. The activity served as a tool to bridge the gap between the Academe and the Food Industry wherein the author was assigned as a quality assurance inspector in a slaughtering and eat processing line. Though training and exposure during the plant practice, the author was able to undertake quality control and quality assurance procedures that allowed the author to put into practice the technical knowledge of food science and technology. Furthermore, the author acquired new knowledge and gained skills during the raw material testing, production monitoring, chemical and laboratory analysis done in the plant. The author after having studied and experienced the activities in the plant made this manuscript to document the author?s experience during the plant practice and to present a complete technical analysis of the different operations in a meat processing plant